Overview of Measles - Sarawarastri, Nian (Jurnal KESANS : Kesehatan dan Sains, 2023)
Rubeola, also known as measles, that can lead to serious complications and death and one of the world’s most contagious viral diseases. Immunisation against measles started in the 1960s and has dramatically reduced the incidence of measles. The virus, which produces a distinct rash that appears within days of exposure, can spread quickly, and can produce severe complications. Treatment is mainly symptomatic, preventing and controlling dehydration, providing adequate nutrition, and infection control measures. Vaccination is the most effective way to prevent measles virus infection.